Development and Validation of a Process-Based Assessment System for E-Commerce Curricula: A Hybrid AHP--FCE Approach - Wang, Jin; Zhang, Qian; Li, Bo (Education Insights, 2026)
This study proposes the Process-Based Assessment System (PBAS) tailored specifically for "theory-practice" integrated curricula, utilizing the E-commerce major in application-oriented universities as a comprehensive case study. As higher education increasingly emphasizes practical competencies alongside theoretical knowledge, traditional evaluation metrics often fall short in capturing the multifaceted nature of student development. To address this critical gap, the Analytic Hierarchy Process (AHP) is employed to systematically determine the precise weights of various evaluation indices, ensuring a balanced and objective assessment framework. Furthermore, the system's practical feasibility and educational impact are rigorously validated through extensive empirical evidence gathered from classroom implementations. The quantitative and qualitative results demonstrate that by seamlessly integrating observable student behaviors, interactive learning processes, and internal cognitive mechanisms, the PBAS successfully achieves both longitudinal tracking and transversal interaction throughout the entirety of the students' learning journey. This hierarchical, progressive, and highly dynamic evaluation model effectively reflects the continuous development of students' knowledge transfer capabilities. Moreover, it meticulously tracks nuanced learning behaviors, thereby significantly stimulating academic engagement and fostering a culture of autonomous, self-directed learning among students. Consequently, the proposed framework provides a robust, data-driven basis for continuous curriculum optimization through deep pedagogical reflection. Ultimately, the findings highlight that the PBAS demonstrates superior practical applicability, enhanced educational value, and greater scientific rigor when directly compared to conventional, outcome-focused assessment methods.